Parents’ recalled experiences of the child centred health dialogue in children with overweight: a qualitative study - Malin Åsberg; Mariette Derwig; Charlotte Castor (BMC Health Services Research, 2023)
Abstract Background Because overweight and obesity are still increasing and prevention of childhood obesity is more likely to be effective when initiated in preschool children, the Child Health Service in the south of Sweden developed a structured child-centred health dialogue model targeting all 4-year-old children and their families. The aim of this study was to describe parents’ recalled experiences of this health dialogue in children with overweight. Methods A qualitative inductive approach with purposeful sampling was used. Thirteen individual interviews with parents (including 11 mothers and 3 fathers) were conducted and analysed with qualitative content analysis. Results The analysis resulted in two categories: ‘A valuable visit with a subtle individual impact’ that described parents’ recalled experiences of the health dialogue and ‘There is a complex interaction between weight and lifestyle’ that reflected the parents’ perceptions of the relationship between their children’s weight and lifestyle. Conclusions Parents recalled the child-centred health dialogue as important and described discussing a healthy lifestyle as one of the obligations of the Child Health Service. Parents wanted confirmation that their family lifestyle was healthy; however, they did not want to discuss the relationship between their family lifestyle and their children’s weight. Parents expressed that when their child followed the child’s growth curve, then this indicated healthy growth. This study supports using the child-centred health dialogue as a model to provide structure for discussing a healthy lifestyle and growth but highlights the difficulties of discussing body mass index and overweight, especially in the presence of children.